Music Therapy in the Treatment of Dementia: A Systematic Review and Meta-Analysis - Moreno-Morales, Celia; Calero, Raul; Moreno-Morales, Pedro; Pintado, Cristina (Frontiers in Medicine, 2020)
Background: Dementia is a is a neurological condition characterised by deterioration in cognitive, behavioural, social and emotional functions. Pharmacological interventions are available but have limited effect in treating many of the disease’s features. Several studies have proposed the therapy with music as a possible strategy to slow down cognitive decline and behavioural changes associated with ageing in combination with the pharmacological therapy. Objective: To perform a systematic review and subsequent meta-analysis to check whether the application of music therapy in people living with dementia has an effect on cognitive function, quality of life and/or depressive state. Methods: The databases used were Medline, Pubmed Central, EMbase, PsycInfo and the Cochrane Library. The search was made of all the literature until present. For the search, key terms, such as “music”, “brain”, “dementia” or “clinical trial” were used. Results: Finally, a total of 8 studies were included. All the studies have an acceptable quality based on the score on the PEDro (Physiotherapy Evidence Database) and CASP (Critical Appraisal Skills Program) scales. After meta-analysis, it was shown that the intervention with music improves cognitive function in people living with dementia, as well as in the quality of life after the intervention and in long-term depression. Nevertheless, it wasn´t shown any evidence of improvement of the quality of life at long-term and at short-term depression. Conclusion: Based on our results, music could be a powerful treatment strategy. However, it is necessary to develop clinical trials aimed to design standardized protocols depending on the nature or stage of dementia in order to its application together with current cognitive-behavioural and pharmacological therapies.